PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Lika Apreasta; Rendi Marlianda; Serli Adinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by a learning process that has not shown interesting progress and has not been able to encourage active student participation. This situation indirectly has a negative effect on students' reading abilities in Indonesian language subjects, which are still relatively low. Therefore, efforts are needed to use more innovative and interesting learning models to improve students' reading skills in Indonesian language subjects. This research aims to determine whether there is an influence of the Scramble Type Cooperative Learning Model on the Beginning Reading Ability of Class II Elementary School Students. This research is experimental research using a quasi-experimental research design, with a nonequivalent control group design. The research location was carried out at SDN 10 Sitiung and SDN 07 Sitiung, Sitiung sub-district, Dharmasraya Regency. The research sample consisted of 25 students who were class II students. The data collection instrument used is a performance test using a questionnaire that has been validated by expert lecturers. The results of this research show that the average posttest score for the control class is 71 and the average for the experimental class is 79. Hypothesis testing uses an independent sample test from the calculation results obtained sig < (0.000 < 0.05) which means rejecting the existence of H0 and accepting Ha, which means there is an influence of the scramble type cooperative learning model in class II elementary school.